21st Century Learning Trends : What Educators Need to Know - Ranggana, Alfaza; Wahyudin, Wahyudin; Gunarso, Gunarso; Permatasari, Endah (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2024)
In the 21st century, a paramount emphasis lies on the education of the 21st century and the cultivation of multifaceted skills that bolster students in acclimating to dynamic transformations. A pivotal trajectory in educational paradigms manifests through the amalgamation of technology and the adoption of digital pedagogical methodologies. The transition towards this technological integration is propelled by the imperative to assimilate 21st-century proficiencies, fortifying students for an ever-evolving technological milieu. Concurrently, there is an accentuation on honing students' faculties of critical reasoning and amplifying scientific acumen. Character education assumes a centrality, underscoring its resonance with the perspectives of students navigating the complexities of the 21st century. Moreover, 21st-century education encompasses the advocacy for innovative aptitudes and entrepreneurial prowess. Global educational trends steer towards STEM-oriented frameworks, augmenting students' adeptness in science, technology, engineering, and mathematics. In summation, education in the 21st century is intricately entwined with technology, globalization, and the imperative for students to foster competencies germane to an expeditiously evolving world.